2009
DOI: 10.1159/000262313
|View full text |Cite
|
Sign up to set email alerts
|

EEG Power Spectrum to Predict Prognosis after Hemicraniectomy for Space-Occupying Middle Cerebral Artery Infarction

Abstract: Background: Early prediction of outcome after decompressive surgery for space-occupying middle cerebral artery (MCA) infarction is needed to guide further therapy. Here we applied spectral EEG analysis to determine the prognosis early after hemicraniectomy, while the patient is still treated in the intensive care unit. Methods: Continuous EEG monitoring following hemicraniectomy was performed in 10 patients with space-occupying MCA infarction. All patients were analgosedated and mechanically ventilated. The fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 55 publications
1
8
0
Order By: Relevance
“…Negative correlation between alpha activity and stroke outcome is in accordance with several previous studies (Sainio et al, 1983;Szelies et al, 2002;Cuspineda et al, 2007;Finnigan et al, 2007;Diedler et al, 2010;Schleiger et al, 2014). Alpha frequencies are thought to derive from cortical layers IV and V, whereas slower delta or theta frequencies are generated by the thalamus and cortical layers II-VI (Schuijt et al, 2012).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Negative correlation between alpha activity and stroke outcome is in accordance with several previous studies (Sainio et al, 1983;Szelies et al, 2002;Cuspineda et al, 2007;Finnigan et al, 2007;Diedler et al, 2010;Schleiger et al, 2014). Alpha frequencies are thought to derive from cortical layers IV and V, whereas slower delta or theta frequencies are generated by the thalamus and cortical layers II-VI (Schuijt et al, 2012).…”
Section: Discussionsupporting
confidence: 91%
“…In general, EEG parameters such as total power, relative delta and alpha power, ratios between slower and faster frequencies (such as the delta/alpha ratio [DAR] and the [delta + theta/alpha + beta] ratio [DTABR]), and brain symmetry indices (such as the Brain Symmetry Index [BSI] and pair-derived BSI) have been strongly associated with stroke outcome, for up to 12 months (Finnigan and van Putten, 2013). These measures have also been shown, in some studies, to be more reliable in prognostication than standard clinical evaluation (Cuspineda et al, 2003;Finnigan et al, 2007;Diedler et al, 2010;Sheorajpanday et al, 2010Sheorajpanday et al, , 2011b or imaging biomarkers (Finnigan et al, 2004;Sheorajpanday et al, 2010Sheorajpanday et al, , 2011b.…”
Section: Introductionmentioning
confidence: 99%
“…Prognostication Following hemicraniectomy for spaceoccupying middle cerebral artery infarction, the presence of faster EEG activity was associated with good recovery in patients monitored with cEEG [50]. Three studies have demonstrated that the disappearance or further slowing of delta activity in the acute phase (within 24 h) of AIS predicted a malignant course (cerebral edema) [51][52][53].…”
Section: Eeg In Patients With Aismentioning
confidence: 99%
“…In a different patient population of 10 analgosedated and mechanically ventilated patients with hemicraniectomy after severe middle cerebral artery stroke, there was a statistically significant association between the presence of 5-to 10-Hz EEG activity in quantitative EEG analysis and favorable functional outcome. 33 Another study focusing on patients with severe ischemic stroke, showed a statistically significant correlation between poor functional outcome and RAWOD. 34 The aforementioned studies are summarized in Table 1.…”
Section: Functional Outcomementioning
confidence: 99%